The positive role of authentic leadership in organizations negatively affected by cognitive diversity - Yagi, Kaori; Iida, Junko; Fuji, Kei (Frontiers in Psychology, 2024)
Workplace diversity has recently gained increasing significance and urgency in business organizations. This promotion may stem from information processing, and specifically from information elaboration. Information elaboration leverages diverse task-related information and skills possessed by members, fostering the exchange of diverse perspectives, elaborate discussions, and achieving high team performance. In this context, cognitive diversity, encompassing members’ knowledge, skills, and perspectives, may have a positive impact. However, some previous studies suggest that cognitive diversity can lead to affective conflict and impede information processing. In organizations with highly homogeneous social and cultural backgrounds, cognitive diversity may not be effectively utilized in the information elaboration process, potentially yielding negative effects. Authentic leadership is recognized as a significant contributor to facilitating team processes including information processing, with various studies demonstrating its effectiveness. This study hypothesized that cognitive diversity negatively affects the information elaboration process, while authentic leadership has a positive effect. To test these hypotheses, we employed multilevel structural equation modeling analysis based on data collected from 375 respondents in 90 teams across various industries in Japan. The results showed that cognitive diversity negatively affects information elaboration at the individual level. By contrast, authentic leadership positively affects information elaboration at both individual and team levels. These findings suggest that the effect of cognitive diversity on information processing in the workplace may not always be positive, particularly in a sociocultural context that values homogeneity, as observed in Japanese organizations. This study advances the literature on authentic leadership by validating its effect on information elaboration and provides practical implications for diversity management. Additionally, it underscores the effectiveness of authentic leadership in leveraging team members’ cognitive diversity to facilitate information elaboration.